Nitrogen Fertilizer Sources: What Does The Future Hold for Citrus Producers? - Tom Obreza; Larry Parsons; Kelly Morgan (EDIS, 2006)
Florida citrus growers are well aware that nitrogen (N) is the single most important nutrient applied as a fertilizer to assure maximum yield and fruit quality. Most growers are probably also aware of the substantial N fertilizer price increases that have occurred during the past year (Table 1). Ammonium nitrate, the workhorse N fertilizer used by citrus growers for decades, has had the greatest leap in cost. Typical questions on the minds of growers these days are: why has this happened, will it continue, and will economics force a change in the type of N fertilizer we use?  This document is SL-238, one of a series of the Department of Soil and Water Sciences, UF/IFAS Extension. Original publication date February 2006.